فعالية برنامج علاجي قائم على مهارات ما وراء الذاكرة وأثره على الذاكرة العاملة لدى المعسرين قرائيا (مجلة الواحات للبحوث والدراسات, 2021)
The Purpose Of This Study Is To Determine The Efficacy Of A Proposed Therapeutic Program Based On The Process Of Metamemory And To Study Its Effect On The Increase Of The Working Memory Activity Of Dyslexic Students. The Program Applies To A Sample Of Grade 5 Students With Reading Disabilities. To This End, The Researcher Has Designed A Program In Light Of The Theoretical Frameworks Of Working Memory And Previous Studies In This Field, Makes Students Aware Of How Working Memory Works, Teaches Them About Training Strategies And How They Work. Learns The Means To Choose The Strategy Best Suited To The Educational Situation. Keywords   - Metamemory, Working Memory, Dyslexia, Therapeutic Program, Efficiency.